2022
DOI: 10.1001/jamanetworkopen.2022.39860
|View full text |Cite
|
Sign up to set email alerts
|

Association of Promoting Housing Affordability and Stability With Improved Health Outcomes

Abstract: ImportanceHousing insecurity—that is, difficulty with housing affordability and stability—is prevalent and results in increased risk for both homelessness and poor health. However, whether interventions that prevent housing insecurity upstream of homelessness improve health remains uncertain.ObjectiveTo review evidence characterizing associations of primary prevention strategies for housing insecurity with adult physical health, mental health, health-related behaviors, health care use, and health care access.E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 64 publications
2
16
0
Order By: Relevance
“…Furthermore, housing voucher funding remains inadequate to meet the nation’s housing need . Whereas traditional methods of supporting housing security have modest associations with health outcomes, decisive, drastic, tenant-friendly housing policies have been associated with significant health outcomes in the COVID-19 pandemic. Specifically, eviction moratoria have been found to be associated with decreasing SARS-CoV-2 transmission, reducing COVID-19 mortality, and supporting adult mental health .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, housing voucher funding remains inadequate to meet the nation’s housing need . Whereas traditional methods of supporting housing security have modest associations with health outcomes, decisive, drastic, tenant-friendly housing policies have been associated with significant health outcomes in the COVID-19 pandemic. Specifically, eviction moratoria have been found to be associated with decreasing SARS-CoV-2 transmission, reducing COVID-19 mortality, and supporting adult mental health .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, housing voucher funding remains inadequate to meet the nation's housing need. 70 Whereas traditional methods of supporting housing security have modest associations with health outcomes, 61,71 decisive, drastic, tenant-friendly housing policies have been associated with significant health outcomes in the COVID-19 pandemic.…”
Section: Implications For Practice and Policymentioning
confidence: 99%
“…Specifically, programs that target unmet food, housing, and transportation needs have been demonstrated to improve health outcomes. 22,25,29 For example, a retrospective cohort study found that 54 low-income patients enrolled in a healthy food incentive program had a mean reduction of 0.74 kg/m 2 in body mass index, compared with age-matched, ethnicitymatched, and comorbidity status-matched control patients who had a mean increase of 0.35 kg/m 2 . 30 In addition, by conducting a randomized controlled trial, Wolitski et al 31 found that patients with housing instability who were provided immediate Housing Opportunities for People with AIDS (HOPWA) rental assistance had significant improvements in patient-reported physical and mental health, compared with patients who were not provided housing assistance.…”
Section: Discussionmentioning
confidence: 99%
“…Assessment of SDOH needs provides targets for interventions that can be implemented on an individual level to address unmet social needs with potential improvement in health status. Specifically, programs that target unmet food, housing, and transportation needs have been demonstrated to improve health outcomes 22,25,29 . For example, a retrospective cohort study found that 54 low-income patients enrolled in a healthy food incentive program had a mean reduction of 0.74 kg/m 2 in body mass index, compared with age-matched, ethnicity-matched, and comorbidity status-matched control patients who had a mean increase of 0.35 kg/m 2 30 .…”
Section: Discussionmentioning
confidence: 99%
“…One exception is a cluster randomized trial in Philadel phia 380 , which reported lower depressive symptoms and improved selfworth amongst residents in intervention settings where a green ing initiative focused on improving the physical quality of the built environment by planting trees, removing litter, and landscaping vacant land in urban settings. A recent review of interventions to promote housing affordability and stability found no evidence of improved mental health outcomes in selective populations (par ticularly homeless and Veteran groups) 381 .…”
Section: Neighbourhood Interventionsmentioning
confidence: 99%